2003
DOI: 10.1213/01.ane.0000049682.48703.44
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Spinal Bupivacaine in Combination with Either Epidural Clonidine and/or 0.5% Bupivacaine Administered at the Incision Site on Postoperative Outcome in Patients Undergoing Lumbar Laminectomy

Abstract: Spinal anesthesia with supplemental epidural clonidine in combination with incision site subcutaneous bupivacaine was evaluated both intra- and postoperatively and compared with spinal anesthesia alone for lower lumbar spine procedures. Both epidural clonidine and subcutaneous incisional bupivacaine, added to spinal anesthesia for lumbar spine surgery, improves pain relief and reduces the need for postoperative opioids with their associated side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Epidural clonidine is thought to produce analgesia in part by mimicking the action of spinally released norepinephrine from descending noradrenergic inhibitory pathways and by activating spinal cholinergic interneurons through interaction with presynaptic and postsynaptic a 2 -adrenoceptors on afferent neurons in the superficial dorsal horn of the spinal cord [15,16]. It is commonly used in association with local anesthetics and other analgesic drugs to enhance the quality and duration of extradural analgesia in the postoperative period [17,18]. As of writing, the dose of epidural clonidine to achieve good pain relief without deleterious side effects remains undetermined [17].…”
Section: Discussionmentioning
confidence: 99%
“…Epidural clonidine is thought to produce analgesia in part by mimicking the action of spinally released norepinephrine from descending noradrenergic inhibitory pathways and by activating spinal cholinergic interneurons through interaction with presynaptic and postsynaptic a 2 -adrenoceptors on afferent neurons in the superficial dorsal horn of the spinal cord [15,16]. It is commonly used in association with local anesthetics and other analgesic drugs to enhance the quality and duration of extradural analgesia in the postoperative period [17,18]. As of writing, the dose of epidural clonidine to achieve good pain relief without deleterious side effects remains undetermined [17].…”
Section: Discussionmentioning
confidence: 99%
“…Jellish et al 7 and Rung et al 14 compared GA and SA in LDS and found that SA was superior to GA with respect to easy application, cost effectiveness, and low environmental pollution. In addition, since these operations are usually performed in the prone position, the awake patient can self-position to avoid nerve injury to the brachial plexus and pressure necrosis to the face, which may occur in the malpositioned patient under GA. 7 In a study of 120 patients Jellish et al 19 determined that epidural clonidine as a supplement to SA produced no perioperative complications and improved postoperative pain and hemodynamic stability in patients undergoing lower spinal procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Jellish et al used spinal bupivacaïne in combination with epidural clonidine 150-300 µg in patients undergoing lumbar laminectomy. They found that epidural clonidine enhanced the sensory blockade of bupivacaïne and produced better hemodynamics postoperatively while there was no difference in the incidence of intra-operative hypotension or bradycardia between the clonidine and the control group [52].…”
Section: Epidural Analgesiamentioning
confidence: 99%
“…Less commonly used adjuvant substances, used either alone or in combination are clonidine [51][52][53], methylprednisolone [54,55] and midazolam [56]. Bonhomme et al found the combination of clonidine with morphine to be superior to a combination with bupivacaine [51].…”
Section: Epidural Analgesiamentioning
confidence: 99%
See 1 more Smart Citation